Lao People's Democratic Republic : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Lao People's Democratic Republic during 1996. The paper notes that real GDP growth of nearly 7 percent was readied despite disappointing growth in the agricultural sector in the aftermath of the floods. It highlights that the significant reduction in inflation in 1996 was brought about despite significant hikes in food prices as a result of those floods. The paper also indicates how the 1995/96 budget contributed to the financial tightening needed after the 1995 surge in inflation.